Analysis of Entrepreneurial Competency in East Java - Esti Nalurani; Fendy Suhariadi; Rahma Sugihartati (Research Synergy Foundation, 2021)
Based on the 2018 Global Entrepreneurship Index’s data, globally, Indonesia is a country that has a low number of entrepreneurs, which position in 94 from 137 countries. Meanwhile, entrepreneurs have an important role in supporting the national economy in various aspects. Indirectly, they are required to have more competence to compete and survive longer. This research finds out the relevance of 30 characteristics in the three-cluster entrepreneurial competence block diagram for entrepreneurs in East Java. The authors use the qualitative method with the Miles and Huberman analysis technique. This data was collected by interviewing 11 entrepreneurs who have been selected based on the criteria. With the approach of Miles and Huberman, the researcher concluded that 11 entrepreneurs had 30 entrepreneurial characteristics and considered that these characters were important. The results identify that 30 characteristics in the three-cluster entrepreneurial competency block diagram are valid. In addition, the competence of entrepreneurs can be through a religious approach and the culture of the surrounding community. And during the pandemic, entrepreneurial competence is more relevant with the government and society support.